2014
DOI: 10.1177/0261018314545597
|View full text |Cite
|
Sign up to set email alerts
|

Let’s get real about the ‘riots’: Exploring the relationship between deprivation and the English summer disturbances of 2011

Abstract: Despite media and political rhetoric to the contrary, there is persuasive evidence to suggest an association between deprivation and those involved in the English riots of 2011, which continues to be downplayed when developing responses to crime and crime prevention policy. This study explores empirical evidence from two major cities in the North West of England, which highlights an association between deprivation and rioting in both criminal charge and sentencing data allowing further exploration of some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Most of Newburn et al's (2018) interviewees reported police discrimination, often based on racism, and many felt alienated from authority more broadly. Deprivation was also a predictor of participation (Kawalerowicz & Biggs, 2015;Lightowlers, 2015).…”
Section: Patterns Of Collective Behaviour In the 2011 English Riotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of Newburn et al's (2018) interviewees reported police discrimination, often based on racism, and many felt alienated from authority more broadly. Deprivation was also a predictor of participation (Kawalerowicz & Biggs, 2015;Lightowlers, 2015).…”
Section: Patterns Of Collective Behaviour In the 2011 English Riotsmentioning
confidence: 99%
“…Most of Newburn et al's () interviewees reported police discrimination, often based on racism, and many felt alienated from authority more broadly. Deprivation was also a predictor of participation (Kawalerowicz & Biggs, ; Lightowlers, ). Moreover, targets of looting and property damage often reflected anti‐corporate attitudes (Ball & Drury, ) or desire to control familiar space (Tiratelli, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies identi ed ACEs as signi cant risk factors for weapon-related crime, which strongly supports the relationship between early childhood trauma and violence. It can be argued that trauma and an unstable family life create an environment which is likely to manifest aggression and poor mental health, increasing the risk of violent behaviour (34) . This coincides with previous knowledge regarding the long-term effects of traumatic childhood on health within adulthood, including economic deprivation, anxiety, and aggression (36)(37) .…”
Section: Adverse Childhood Experiencesmentioning
confidence: 99%
“…Research on riots indicates several factors that help understand why rioting is more likely to attract persons living in poorer and marginalized residential areas (Lightowlers 2015;Kawalerowicz and Biggs 2015). Case studies stress contextual factors, such as intergroup relations and frequency of inter-group violence (Sen 2008, 10), competition over scarce resources, such as housing and employment (Olzak, Shanahan, and McEneaney 1996), and the consequences of "resignation" (Abbink, Masclet, and Mirza 2011, 19).…”
Section: Previous Researchmentioning
confidence: 99%